Impact of Seawater Temperature on Coral Reefs in the Context of Climate Change. A Case Study of Cu Lao Cham – Hoi An Biosphere Reserve - Dao, Hung N.; Vu, Hang T.; Kay, Susan; Sailley, Sevrine (Frontiers in Marine Science, 2021)
Coral reefs are a natural habitat for many species, as well as being of high economic and touristic significance. However, they represent an extremely sensitive ecosystem with a narrow ecological limit: prolonged high temperatures can lead to bleaching, in which corals expel their symbiotic algae and eventually corals will degrade and die. Based on climate change projections from the Blue Communities regional model, using linear regression, exponential regression, polynomial regression, we found that by the decades 2041–2050 and 2051–2060, whether with RCP 4.5 or RCP 8.5, the environmental temperature will change beyond the coral capacity threshold. Of particular concern is RCP 8.5, where the number of weeks per decade in which SST exceeds the threshold of coral reef bleaching is up to 55, compared to 0 at the beginning of the century. As well, the El Niño phenomenon often heats up waters to abnormally high temperatures in Cu Lao Cham and, it is projected to rise even further. Consequently, the combination of climate change and El Niño will cause abnormal increases in the seawater environment beyond the coral resistance threshold, leading to degradation of this internationally important site. Decisive and practical action must be taken to deal with climate change in this part of the world.